Single multiplex polymerase chain reaction for environmental surveillance of toxigenic-pathogenic O1 and non-O1 Vibrio cholerae - Goel, A K; Ponmariappan, S; Kamboj, D V; Singh, L (Folia microbiologica, 2007)
A multiplex PCR assay was developed for the detection of toxigenic and pathogenic V. cholerae from direct water sources using specific primers targeting diverse genes, viz. outer membrane protein (ompW), cholera toxin (ctxB), ORF specific for O1 (rfbG), zonula occludens (zot) and toxin co-regulated pilus (tcpB); among these genes, ompW acts as internal control for V. cholerae, the ctx gene as a marker for toxigenicity and tcp for pathogenicity. The sensitivity of multiplex PCR was 5 x 10(4) V. cholerae cells per reaction. The procedure was simplified as direct bacterial cells were used as template and there was no need for DNA extraction. The assay was specific as no amplification occurred with the other bacteria used. Toxigenic V. cholerae were artificially spiked in different water samples, filtered through a 0.45 microm membrane, and the filters containing bacteria were enriched in APW for 6 h. PCR following filtration and enrichment could detect as little as 8 V. cholerae cells per mL in different spiked water samples. Various environmental potable water samples were screened for the presence of V. cholerae using this assay procedure. The proposed method is rapid, sensitive and specific for environmental surveillance for the presence of toxigenic-pathogenic and nonpathogenic V. cholerae.
Keywords: Environmental Monitoring; polymerázová řetězová reakce; Water Pollutants; Bacterial Proteins; monitorování životního prostředí; Vibrio cholerae non-O1; Cholera Toxin; sladká voda; DNA Primers; Fresh Water; zásobování vodou; látky znečišťující vodu; Water Supply; Sensitivity and Specificity; senzitivita a specificita; bakteriální proteiny; Vibrio cholerae O1; DNA primery; Polymerase Chain Reaction; cholerový toxin